Perancangan Presensi QR Code Berbasis Web Pada Diaz Plastik Dengan Metode Waterfall - Albi Gunawan, Zein; Sulthoni Nabhan, Fathih; Akbar Syamputra, Raihan; Lutfi Fuadi, Achmad (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
Employee attendance is a crucial aspect in supporting smooth operations and maintaining work discipline. However, the manual attendance method still used at Diaz Plastik Store is prone to data loss, attendance manipulation, and complicates the process of recapitulating and monitoring dynamic shift schedules. This research aims to design a web-based employee attendance system integrated with QR Code technology and shift information to improve the efficiency and accuracy of attendance recording. The system is developed using the Waterfall method with stages including requirements analysis, system design, implementation, testing, and maintenance. The attendance process involves user login, followed by scanning a QR Code generated by the admin, enabling real-time attendance data recording linked with assigned shift schedules. The resulting system is expected to overcome the weaknesses of the manual method, accelerate data recapitulation, and assist Diaz Plastik Store management in objectively and timely evaluating employee performance, thereby supporting more effective decision-making related to human resource management.